The digital matte painting handbook - Mattingly, David B., 1956- (Wiley, 2011)
"The only how-to guide dedicated to mastering the technique of digital matte painting!Matte painting affords seamless integration between an artist's painting with live action film footage and allows for greater flexibility and creative input in the appearance of movie settings. This unique book reveals a variety of tools and techniques that are both industry and classroom tested and will enhance your existing skill set. Veteran author and instructor David Mattingly walks you through the process of creating a matte painting, starting with rough concept sketches, working out the perspective drawing, adding light and shadow, and texturing all of the elements in the painting. You'll gradually upgrade to using Adobe After Effects and Autodesk Maya in order to fulfill your matte painting vision. Escorts you through the process of creating a matte painting, starting with the initial concept sketch, adding light and shadow, texturing elements, and incorporating motion and depth Author is an experienced matte artist and teacher and shares a plethora of unique industry- and classroom-tested tools and techniques Features helpful step-by-step instructions accompanied by screen shots and photos to illustrate the process of creating a matte painting Whether you're creating a background for a studio production, independent film, TV commercial, or YouTube video, The Digital Matte Painting Handbook helps you successfully complete your project"--Resumé vydavatele
Obsahuje rejstřík
Keywords: digitální kinematografie; filmové efekty; filmový obraz; digitální zpracování obrazu; digital cinematography; film effects; cinematographic image; digital image processing; příručky; handbooks, manuals, etc